The Lithofacies Association of Brown Shales In Kiliran Jao Subbasin, West Sumatra Indonesia - Edy Sunardi (Geological Agency, 2015)
DOI:10.17014/ijog.2.2.77-90The lithofacies association, mainly lithology and depositional sequences of the Brown Shale Unit of Pematang Group was studied based on recent fieldwork at Karbindo Coal Mine, in Kiliran Jao Subbasin,West Sumatra, Indonesia. The lower part of the Brown Shale Unit consists of coal and limestone facies which were deposited in a marginal lacustrine area. The limestone was generated by evaporatic processes characterized by the presence of primary calcite crystals. The upper part of the unit, from bottom to top, is composed of six facies associations, among all: amalgamated massive thick bedded shales, interlaminated shales and siltstones, interbedded grey and red shales, fossiliferous shales, massive thick bedded shales, and interlaminated shale and sandstone facies. Those facies were deposited in a shallow to deep water lacustrine environment, characterized by their lithology compositions, sedimentary structures, and fossil contents. The unit has such as high content of reworked organic matters-bearing shales and mudstones. Turbiditic sedimentary structures, gastropods, and bivalves are common.